Dampak Perceraian Terhadap Kondisi Psikologis Keluarga di Kecamatan Muara Dua Kota Lhokseumawe - Fadila; Nazaruddin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study examines the psychological impact of divorce on family members in Muara Dua District, Lhokseumawe City. Using a qualitative approach, data were collected through in-depth interviews, observations, and documentation involving divorced families in Meunasah Mesjid, Panggoi, and Uteunkot—villages with the highest divorce rates. The findings reveal that divorce generates severe psychological distress across family members. Former spouses experience stress, feelings of failure, and social instability, while children show symptoms of trauma, anxiety, and declining academic performance. Divorce thus emerges not merely as a legal act but as a systemic disruption of family emotional equilibrium. The study underscores the need for preventive interventions such as family counseling, social mediation, and the strengthening of religious and legal institutions to foster family resilience. By integrating psychological and Islamic legal perspectives within the Acehnese socio-cultural context, this research provides a distinctive theoretical contribution to Islamic family law and family psychology. It also offers practical recommendations for the Mahkamah Syar’iyah to develop more contextual and preventive frameworks for addressing the psychological consequences of divorce.